Cultural diplomacy through cinema : the case of the french cinematographic “Exception” in the era of globalization - Franco, Ottavia di (2023)
This internship report comprehensively investigates the roles of French cinema in shaping national identity through cultural diplomacy and its response to globalization and Hollywood's influence. It highlights key historical developments, including the Lumière Cinematograph and the French New Wave, showcasing France's cinematic legacy and its unique "cinematographic culture." Furthermore, the study closely examines the State's active involvement in supporting the French film industry, scrutinizing government actions contributing to its enduring presence. It also explores how the French film industry strategically responds to global challenges, revealing its adaptive strategies. Through a content analysis approach, this research deeply explores two auteur films to uncover the unique qualities of French cinema, particularly within the global context. Ultimately, it demonstrates how France's commitment to its cultural heritage and strategic use of cinema as a diplomatic tool position it as a prominent global cultural center. France successfully maintains its cultural diversity and artistic expression while appealing to a broader international audience, emphasizing the significance of French cinema in preserving and promoting cultural diversity and safeguarding cultural identity on the global stage.